2016
DOI: 10.1002/ccd.26443
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between chronic obstructive pulmonary disease and transcatheter aortic valve implantation—A systematic review and meta‐analysis

Abstract: COPD is common among patients undergoing TAVI, and COPD impacts both short- and long-term survival. COPD patients, who had a lower BMI, shorter distance of 6MWT and CKD, were at higher risk for TAVI futility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 53 publications
3
29
0
Order By: Relevance
“…Currently, TAVR is a treatment modality for patients with severe aortic stenosis, especially those who are at prohibitive or high surgical risk . A number of comorbid conditions have been associated with increased morbidity and mortality after TAVR . However, there are contradicting data on the impact of DM on post‐TAVR outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, TAVR is a treatment modality for patients with severe aortic stenosis, especially those who are at prohibitive or high surgical risk . A number of comorbid conditions have been associated with increased morbidity and mortality after TAVR . However, there are contradicting data on the impact of DM on post‐TAVR outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 A number of comorbid conditions have been associated with increased morbidity and mortality after TAVR. [18][19][20][21] However, there are contradicting data on the impact of DM on post-TAVR outcomes.…”
Section: Major Vascular Complicationsmentioning
confidence: 99%
“…More recently Poulsen et al, have evidenced that, in patients with severe AS treated with TAVI, the presence of COPD affects neither overall survival nor survival from cardiac death. However, other authors have demonstrated a significantly higher mortality among TAVI patients with COPD compared with those without this condition . Despite this, Dziewierz et al did not found differences in mortality between patients with and without COPD after adjustment for most of the frailty indices.…”
Section: Discussionmentioning
confidence: 89%
“…Patients with AS are usually older and often present with multiple comorbidities. These include chronic obstructive pulmonary disease (COPD), which is present in up to 20% of patients presenting for SAVR and in up 43% of those presenting for TAVI . The higher prevalence of COPD in patients undergoing TAVI vs. SAVR could be explained by the fact that this condition is a major limiting factor in patient selection for surgical intervention …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, chronic lung disease and atrial fibrillation (AF)/flutter were more frequent in patients undergoing TAVI with than without RV dilatation in a study by Ito et al , which are addressed in the Society of Thoracic Surgeons Predicted Risk of Mortality as risk factors of operative mortality. In a meta‐analysis by Liao et al of 28 studies enrolling 51,530 patients undergoing TAVI, prevalence of chronic obstructive pulmonary disease ranged from 12.5 to 43.4%, and it was associated with increased 30‐day and > 2‐year all‐cause mortality and 30‐day and 1‐year cardiac mortality after TAVI.…”
Section: Discussionmentioning
confidence: 99%